PELATIHAN BUSINESS MODEL CANVAS BAGI SISWA SMAN 1 GIANYAR DALAM MEMBANGUN BISNIS DI USIA DINI - Nyoman Purnama (LPPM Universitas Bina Bangsa, 2024)
In the era of globalization and rapid technological development, entrepreneurial skills are becoming increasingly important. At the Senior High School (SMA) level it has been designed to prepare students to continue to the higher education or entrepreneurship. Entrepreneurship is one way to avoid unemployment in productive age. The community service activities carried out by the team from Primakara University at SMAN 1 Gianyar aim to equip every student who has an entrepreneurial spirit to be able to understand and apply their business ideas using the right methods. In this community service activity, a business planning method, namely the Business Model Canvas (BMC), was introduced. The Business Model Canvas as a management strategy in the form of a visual chart consisting of 9 elements can provide a more comprehensive picture of business planning but is relatively easier to understand and apply. Through this introduction to the Business Model Canvas, SMA 1 Gianyar students can express and apply their business ideas into these 9 elements in a more structured and detailed manner, thus making the process of preparing business proposals easier. From the results of the training and mentoring with Business Model Canvas (BMC) material that was carried out for SMAN 1 Gianyar students, the students were very enthusiastic about expressing their business ideas in a structured and detailed manner